Expression of FcRL4 defines a pro-inflammatory, RANKL-producing B cell subset in rheumatoid arthritis. Issue 5 (15th January 2014) - Yeo, L; Lom, H; Juarez, M; Snow, M; Buckley, C D; Filer, A; Raza, K; Scheel-Toellner, D
Abstract : Objectives: The success of B cell targeting therapies has highlighted the importance of B cells in rheumatoid arthritis pathogenesis. We have previously shown that B cells in the RA synovium are capable of producing pro-inflammatory and bone-destructive cytokines including RANKL. Here we sought to characterise the nature and functional relevance of the RANKL-producing B cell subset in the RA synovium. Methods: Synovial fluid and peripheral blood B cells from patients with RA were analysed by flow cytometry for markers of B cell differentiation and activation and for chemokine receptors. FcRL4 + and FcRL4 − B cells sorted from synovial fluid were analysed for cytokine expression using Taqman low-density arrays. Synovial tissue biopsies obtained from patients with RA were analysed by immunofluorescence for CD20, RANKL and FcRL4. FCRL4 mRNA expression was determined in synovial tissue of RA patients and non-inflammatory control subjects by real-time PCR. Results: RANKL-producing B cells in RA synovial tissue and fluid were identified as belonging to a distinct subset of B cells defined by expression of the transmembrane protein FcRL4. FcRL4+ B cells express a distinct combination of cytokines and surface proteins indicating a function distinct from that of FcRL4− B cells. Notably, FcRL4+ B cells expressed high levels of TNF-α and RANKL mRNA. Conclusions: We have identified a novel pro-inflammatory B cell population in the RA synovium which is defined by expression of FcRL4 and responsible for RANKL production. This B cell population expresses high levels of CD20, and its removal by rituximab may contribute to the anti-inflammatory effect of this drug.